2004
DOI: 10.1016/j.icesjms.2003.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent fractionation of stable oxygen isotopes in otoliths of juvenile cod (Gadus morhua L.)

Abstract: 2004. Temperature-dependent fractionation of stable oxygen isotopes in otoliths of juvenile cod (Gadus morhua L.). e ICES Journal of Marine Science, 61: 243e251.Analysis of stable oxygen isotopes in otoliths is a promising technique for estimating the ambient temperature experienced by fish, but consistent equations relating temperature and fractionation of stable oxygen isotopes in otoliths among different fish species are lacking. Juvenile cod were reared at constant temperatures from 6 to 20(C and the sagit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
156
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(167 citation statements)
references
References 33 publications
5
156
1
Order By: Relevance
“…However, our estimated values of δ c -δ w are consistent with previous studies on different fish species carried out in laboratory conditions (Kalish 1991b, Thorrold et al 1997, Gao et al 2001, Høie et al 2004b). All those investigations concluded that deposition occurs at or near equilibrium in fish otoliths.…”
Section: Environmental Influences On Hake Recruits and Juvenilessupporting
confidence: 92%
See 3 more Smart Citations
“…However, our estimated values of δ c -δ w are consistent with previous studies on different fish species carried out in laboratory conditions (Kalish 1991b, Thorrold et al 1997, Gao et al 2001, Høie et al 2004b). All those investigations concluded that deposition occurs at or near equilibrium in fish otoliths.…”
Section: Environmental Influences On Hake Recruits and Juvenilessupporting
confidence: 92%
“…Since no oxygen isotope fractionation relationship has been established for the European hake, temperature was estimated using the equation resulting from a robust study on another gadoid, Atlantic cod Gadus morhua L. (Høie et al 2004b), with a 0.95 ‰ prediction limit range:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Høie et al 2004b) and the relative metabolic activity (Sherwood & Rose 2003) of the individual (Kalish 1991a,b, Thorrold et al 1997, Campana 1999, Høie et al 2004a, Shephard et al 2007). As the otolith aragonite grows, oxygen isotopes are precipitated in equilibrium with the endolymph fluid, which is itself in isotopic equilibrium with ambient seawater (Kalish 1991a, Thorrold et al 1997, Campana 1999, Høie et al 2004a.…”
mentioning
confidence: 99%